Cardiac involvement in a pediatric patient with COVID‐19: Looking beyond the nonspecific global cardiac injury. Issue 9 (8th August 2020) - Bhansali, Suneet; Minocha, Prashant; Phoon, Colin; Henry, Gillian; Chakravarti, Sujata; Ramirez, Michelle; Bhatla, Puneet
Abstract: We report a case of a 17‐year‐old healthy male presenting with multisystem hyperinflammatory shock temporally associated with COVID‐19. Cardiac involvement was suspected based on evidence of significant cardiac injury (elevated cardiac biomarkers, electrocardiographic and echocardiographic abnormalities). Cardiac magnetic resonance imaging was performed demonstrating global biventricular systolic dysfunction, as well as a small area of T2 hyperintensity and mid‐wall late gadolinium enhancement. This case discusses the varied cardiac involvement in pediatric patients with COVID‐19 infection and highlights that cardiac injury is not just limited to hyperinflammatory syndrome related global dysfunction but a more focal myocarditis can also be seen.